Spontaneous Retroperitoneal Hemorrhage Caused by Segmental Arterial Mediolysis - Phillips, Courtney K (MedReviews, LLC, 2006)
Spontaneous retroperitoneal hemorrhage is a rare clinical entity; signs and symptoms include pain, hematuria, and shock. Spontaneous retroperitoneal hemorrhage can be caused by tumors, such as renal cell carcinoma and angiomyolipoma; polyarteritis nodosa; and nephritis. The least common cause is segmental arterial mediolysis. Although computed tomography is used for the diagnosis of spontaneous retroperitoneal hemorrhage, it can miss segmental arterial mediolysis as the cause of the hemorrhage. The diagnosis of segmental arterial mediolysis as a cause of spontaneous retroperitoneal hemorrhage requires angiography, with pathologic confirmation for a definitive diagnosis.